A review on PLA with different fillers used as a filament in 3D printing. (2022) - Joseph Arockiam, A.; Karthikeyan Subramanian; Padmanabhan, R.G.; Rajeshkumar Selvaraj; Dilip Kumar Bagal; Rajesh, S.
Abstract: Three-dimensional (3-D) printing is the method of forming a three-dimensional element by layering materials. 3-D printing is commonly done with a variety of materials such as ceramics, polymers and metals. Researchers are working to develop biodegradable additives for 3-D printing to provide sustainable additives. Biodegradable polymeric substances are taken into consideration ability 3-D printing substances because of their abundant assets and beneficial properties. Further, due to their multi-functional characteristics, they are also seen as probable contenders to replace petroleum-based polymeric materials. However, some of their properties are inferior to conventional synthetic polymeric materials. Hence, it is investigated by surveying advanced bio-waste polymer as reinforcement materials with polylactic acid (PLA) filaments for the polymer matrix in 3D printable filaments. The mechanical and thermal properties of polylactic acid filaments (PLA) with various types of fillers were examined in this review work. This overview mainly provides support for young researchers engaged in 3D printing using bio-filled composite materials in the area of PLA processing.